2011
DOI: 10.1038/ja.2011.52
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of minocycline combined with fosfomycin against clinical isolates of methicillin-resistant Staphylococcus aureus

Abstract: This study aimed to evaluate the in vitro activity of minocycline combined with fosfomycin against isolates of methicillinresistant Staphylococcus aureus (MRSA). A total of 87 clinical isolates of MRSA collected from three Chinese hospitals were included in the study. The checkerboard method with determination of the fractional IC index (FICI) was used to determine whether antibiotic combinations act synergistically against these isolates. The susceptibility results for minocycline and fosfomycin were interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, synergy was observed with ceftriaxone in a time-kill study (44). (90), and minocycline (87%) (163). Lower synergy was reported with rifampin (50%) (164).…”
Section: Newer Studiesmentioning
confidence: 92%
“…However, synergy was observed with ceftriaxone in a time-kill study (44). (90), and minocycline (87%) (163). Lower synergy was reported with rifampin (50%) (164).…”
Section: Newer Studiesmentioning
confidence: 92%
“…Otherwise, FOS + DOX combination was tested once against 24 isolates of vancomycin-resistant E. faecium, demonstrating to have synergistic or additive effect in most of cases [68]. Finally, when FOS + MIN was tested against MRSA (152, strains, 3 studies) proved to have synergistic effect in numerous cases [18,69,70]. No study reported any case of antagonism.…”
Section: Tetracyclinesmentioning
confidence: 99%
“…Combination antibiotic therapy has also been proposed for the treatment of MRSA based on the in vitro synergistic activity of minocycline plus fosfomycin [57] and linezolid plus fosfomycin [58], as well as on the clinical use of vancomycin plus rifampicin [59], but more evidence is still needed to test these potential combinations.…”
Section: Treatment Of Mdr Gram-positive Vapmentioning
confidence: 99%